Characterizing the physical and mental health profile of children, adolescents and adults with autism spectrum disorder in Spain - Vidriales-Fernández, Ruth; Plaza-Sanz, Marta; Hernández-Layna, Cristina; Verde-Cagiao, María; Benito-Ruiz, Guillermo; Carvajal-Molina, Fernando (Frontiers in Psychiatry, 2023)
This is the first Spanish epidemiologic study addressing the health profile and poor-health exacerbating factors in 2,629 individuals of all ages with autism spectrum disorder (ASD), utilizing information registered to Autismo España’s database (November 2017-May 2020). A descriptive health data analysis was conducted to assess the prevalence of other conditions associated to ASD in the Spanish population. Male-to-female ratio was 4:1. Nervous system disorders (12.9%), mental health diagnoses (17.8%) and other comorbidities (25.4%) were reported. Women, older individuals and those with intellectual disability (ID) were at an increased risk of health comorbidities and psychopharmacological exposure. Women were also more prone to severe intellectual and functional impairment. Nearly all individuals had difficulties in their adaptative functioning, especially those with ID (50% of the population). Almost half of the subjects received psychopharmacological treatments, mostly antipsychotics and anticonvulsants, from infancy and early childhood.